Evaluación de la posición de dominio en el derecho europeo de la competencia. - Uribe Piedrahita, Carlos Andrés (2013)
The study of dominant position from the theory in general to a specific case such as the one mentioned here is mediated by some causes that allow this market position.These causes are identified, first in a desirable way, by the efficiency of the dominant agent and the other hand, not so desirable, by a set of boundaries the other companies find to compete freely. Thus, this document is willing to illustrate the different type of boundaries that could be found in companies facing competitiveness and the treatment they get from the European antitrust authorities.